Analysis of variation of sagittal position of the jaw bones in skeletal class III malocclusion - Stojanović Zdenka; Nikolić Predrag; Nikodijević Angelina; Milić Jasmina; Duka Miloš (Vojnosanitetski Pregled)
Background/Aim. Skeletal Class III malocclusion is a discrepancy in the sagittal jaw relationship, due to imbalances in their development and/or position, resulting in the dominant appearance of the lower jaw in facial profile. The aim of this study was to determine variations in the sagittal position of the jaw bones to the cranial base in subjects with skeletal Class III, for the earliest possible diagnosis of malocclusion. Methods. Fifty children and as many adults with skeletal Class III, both sexes, were examined and selected, based on the findings of sagittal interjaw relationship (ANB) ≤ 0° from the cephalometric analysis of tele-x-ray profile head shots. The subjects were grouped according to age. The first group consisted of children aged 6-12 years, and another group, of adults aged 18-26 years. We measured the angles of maxillary prognathism (SNA), mandibular prognathism (SNB) and ANB. Based on these results, within the respective groups subclassification into the subgroups was done, among which a significant difference measured values was evaluated. In both groups a significant correlation of the determined values was evaluated. Results. An average SNA angle ranged 77.36 ± 3.58 in children and 77.32 ± 4.88 in adults, while an average SNB angle was 79.46 ± 3.91 in the group of children and 81.12 ± 3.76 in adults. An average ANB angle was -2.10 ± 2.07 in children, and -4.00 ± 2.34 in adults. In both groups, a significant correlation between the measured values and a significant difference in the values of all the measured parameters were found between patients from different subgroups (p < 0.01). Conclusion. The most common morphological variation of sagittal position of the upper jaw is its retrognatism, which is equally present in both children and adults. Sagittal position of the lower jaw in most of the adults was prognathic, while mandible prognathism in the children was less present.